Integral mean of Green’s potentials and their conjugate - Vasyl'kiv, Ya.V.; Kravec, M.Ya. (Carpathian Mathematical Publications, 2013)
The best possible estimates for Lebesgue integral means m_q(r,F) (1q<+∞) for the pair of functions F= g+i\:g, here g - Green's potential, g - function conjugate to g, was obtained. It generalizes well-known results of Ya.V. Vasyl'kiv and A.A. Kondratyuk for logarithms B of Blaschke products B in terms of counting function n(r,0,B) (0<r<1) of their zeroes.